MEDAN MAKNA VERBA â€œMENYENTUHâ€ DALAM BAHASA MELAYU DIALEK SAMBAS - Nurhayati, Anita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract One of the Malay language that still used until right now is Malay language in Sambas dialects (BMDS) at Sambas Regency, West Borneo. This research examines the linguistic of BMDS that focused on the terms of the meaning that semantic field of verb ?to touch?. The method in this research is descriptive method with qualitative form research. Data and sources of data in this research are words, phrases, and sentences that spoken by containing terrain verb meaning to touch in BMDS. The technique that used is direct technique such as face to face conversation (interview) with noted technique. The instruments that used to collect the data in this research are recorder, list of questions, list of illustrations, data cards, and stationery. Based on research there are 47 lexeme verbs to touch in BMDS consist 10 lexeme verb touch with tool usage, 28 lexeme verb to touch without tool usage, and 9 lexeme verbs to touch with or without tool usage. The kind of meaning of verb to touch in BMDS was founded consisting of 47 denotative meanings, 47 grammatical meanings, and 16 connotative meanings. Semantic functions of verbs to touch in BMDS was founded are 47 semantic functions. Keywords: Semantics, Meaning Field, to Touch